Epidemiology of sarcopenia among community‐dwelling older adults in Taiwan: A pooled analysis for a broader adoption of sarcopenia assessments - I‐Chien Wu; Cheng‐Chieh Lin; Chao A. Hsiung; Ching‐Yi Wang; Chih‐Hsing Wu; Ding‐Cheng Chan; Tsai‐Chung Li; Wen‐Yuan Lin; Kuo‐Chin Huang; Ching‐Yu Chen; Chih‐Cheng Hsu (2014)
To develop cut-off points of muscle mass, gait speed and handgrip strength; and to examine the prevalence of sarcopenia, and the relationship between sarcopenia stages and functional limitations and disability by using these cut-off points.We pooled individual participant data of 2867 community-dwelling older adults from five cohort studies. We defined the cut-off point of a muscle mass index (ASM/ht(2)) as the values of two standard deviations below the sex-specific means of a young population or as the 20th percentile of the sex-specific distribution in our study population. The gait speed and handgrip strength cut-off points were defined as the 20th percentile of their population distributions. We also measured functional limitations, using the Short Physical Performance Battery, and the number of activities of daily living and instrumental activities of daily living difficulties.We identified the cut-off points of ASM/ht(2), gait speed and handgrip strength. By applying these cut-off points to our study population, the prevalence of sarcopenia varied from 3.9% (2.5% in women and 5.4% in men) to 7.3% (6.5% in women and 8.2% in men). A higher sarcopenia stage was independently associated with a lower summary performance score, as well as more activities of daily living and instrumental activities of daily living difficulties (P < 0.05 for all).The prevalence of sarcopenia in community-dwelling older adults is comparable with those in other populations. A dose-response relationship exists between sarcopenia stages and functional limitations/disability. The European Working Group on Sarcopenia in Older People consensus definition using these cut-off points is suitable for determining sarcopenia cases in the elderly population of Taiwan.